2009
DOI: 10.1016/j.jlumin.2009.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Long lifetime and efficient emission from Er3+ ions coupled to Si nanoclusters in Si-rich SiO2 layers

Abstract: International audienceReactive magnetron co-sputtering of two confocal SiO 2 and Er 2 O 3 cathodes in argon–hydrogen plasma was used to deposit Er-doped Si-rich SiO 2 layers. The effects of the deposition conditions (such as RF power applied on each cathode and total plasma pressure) and annealing treatment (temperature and duration) on structural, compositional and photoluminescence (PL) properties of the layers were examined. It was found that a significant enhancement of both Er 3+ PL intensity and emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A silicon-rich silicon oxide (SRSO) matrix seems to be very promising as an efficient photosensitizer for different rare-earth (RE) ions such as: Nd 3+ [1,2], Tb 3+ [3], or Er 3+ [4,5]. Among these ions, the Er 3+ ion is well known as an alternative to epitaxially grown light sources emitting in the third telecommunication window [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A silicon-rich silicon oxide (SRSO) matrix seems to be very promising as an efficient photosensitizer for different rare-earth (RE) ions such as: Nd 3+ [1,2], Tb 3+ [3], or Er 3+ [4,5]. Among these ions, the Er 3+ ion is well known as an alternative to epitaxially grown light sources emitting in the third telecommunication window [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…PL spectra were studied at different temperatures from the range 20–300 K using the excitation energy 2.33 eV with the aim to avoid the PL bands B1 and B2 from PL spectra and to analyze the types of optical transitions responsible for the bands B3–B5. Note, that PL spectra of these films measured at the excitation energy 3.82 eV in the range 20–300 K were studied by us early . It was shown that the PL bands B1 and B2 did not change their PL peaks with temperatures.…”
Section: Resultsmentioning
confidence: 92%